Circadian Rhythm Disruption Influenced Hepatic Lipid Metabolism, Gut Microbiota and Promoted Cholesterol Gallstone Formation in Mice - He, Chuanqi; Shen, Weiyi; Chen, Chaobo; Wang, Qihan; Lu, Qifan; Shao, Wentao; Jiang, Zhaoyan; Hu, Hai (Frontiers in Endocrinology, 2021)
Background Hepatic lipid metabolism regulates biliary composition and influences the formation of cholesterol gallstones. The genes Hmgcr and Cyp7a1, which encode key liver enzymes, are regulated by circadian rhythm-related transcription factors. We aimed to investigate the effect of circadian rhythm disruption on hepatic cholesterol and bile acid metabolism and the incidence of cholesterol stone formation. Methods Adult male C57BL/6J mice were fed either a lithogenic diet (LD) only during the sleep phase (time-restricted lithogenic diet feeding, TRF) or an LD ad libitum (non-time-restricted lithogenic diet feeding, nTRF) for 4 weeks. Food consumption, body mass gain, and the incidence of gallstones were assessed. Circulating metabolic parameters, lipid accumulation in the liver, the circadian expression of hepatic clock and metabolic genes, and the gut microbiota were analyzed. Results TRF caused a dysregulation of the circadian rhythm in the mice, characterized by significant differences in the circadian expression patterns of clock-related genes. In TRF mice, the circadian rhythms in the expression of genes involved in bile acid and cholesterol metabolism were disrupted, as was the circadian rhythm of the gut microbiota. These changes were associated with high biliary cholesterol content, which promoted gallstone formation in the TRF mice. Conclusion Disordered circadian rhythm is associated with abnormal hepatic bile acid and cholesterol metabolism in mice, which promotes gallstone formation.